2016
DOI: 10.1007/s10120-015-0592-y
|View full text |Cite
|
Sign up to set email alerts
|

Prospero homeobox 1 mediates the progression of gastric cancer by inducing tumor cell proliferation and lymphangiogenesis

Abstract: Background Prospero homeobox 1 (PROX1) functions as a tumor suppressor gene or an oncogene in various cancer types. However, the distinct function of PROX1 in gastric cancer is unclear. We determined whether PROX1 affected the oncogenic behavior of gastric cancer cells and investigated its prognostic value in patients with gastric cancer. Methods A small interfering RNA against PROX1 was used to silence PROX1 expression in gastric cancer cell lines AGS and SNU638. Expression of PROX1 in gastric cancer tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 33 publications
4
30
0
1
Order By: Relevance
“…It has been proposed that PROX1 is essential for lymphatic vascular system development by regulating endothelial cell differentiation and metastatic dissemination (31,32). Interestingly, qRT-PCR and Western blot analyses showed that PROX1 expression was significantly increased in exosomal LNMAT2-treated HLECs as compared with the control-treated HLECs (Figure 8, A and B, and Supplemental Figure 8, E and F), indicating that exosomal LNMAT2 upregulated PROX1 expression in HLECs.…”
Section: Resultsmentioning
confidence: 86%
“…It has been proposed that PROX1 is essential for lymphatic vascular system development by regulating endothelial cell differentiation and metastatic dissemination (31,32). Interestingly, qRT-PCR and Western blot analyses showed that PROX1 expression was significantly increased in exosomal LNMAT2-treated HLECs as compared with the control-treated HLECs (Figure 8, A and B, and Supplemental Figure 8, E and F), indicating that exosomal LNMAT2 upregulated PROX1 expression in HLECs.…”
Section: Resultsmentioning
confidence: 86%
“…Reportedly, PROX1 plays various tumor-dependent functional roles, which reflect both the oncogenic potential and a tumor-suppressive role [90]. In addition, PROX1 promoted cell growth, angiogenesis, and sorafenib resistance in patients with HCC [102,91] and is associated with the lymphangiogenesis, metastasis, and poor prognosis in various malignancies [92,103,104]. However, high PROX1 expression is related to better prognosis for pancreatic and gastric cancer patients [105,106].…”
Section: Novel Prognosticators Of Osccmentioning
confidence: 99%
“…In a zebrafish model, it seems that PROX1 has a dual role in renal development: after its initial roles in the specification of inter-renal primordium, it is critical for the maturation of the inter-renal organ (33). Malignant transformation is followed by up-regulation of PROX1 in tumor cells reported for several types of cancer, such as gastric (34,35), pancreatic (36), vascular (37) and renal (38) cancer. For all these cancer types, PROX1 overexpression is related to high aggressiveness and poor prognosis (35).…”
Section: Comparative Assessment Of Chick Chorioallantoic Membrane (mentioning
confidence: 99%
“…Malignant transformation is followed by up-regulation of PROX1 in tumor cells reported for several types of cancer, such as gastric (34,35), pancreatic (36), vascular (37) and renal (38) cancer. For all these cancer types, PROX1 overexpression is related to high aggressiveness and poor prognosis (35). PROX1 distribution and expression in BHK-21/C13 fibrosarcoma may be considered a promoter of aggressive behavior of these cells, clinically detected during the development of the tumor in both hamster and the chick embryo CAM model.…”
Section: Comparative Assessment Of Chick Chorioallantoic Membrane (mentioning
confidence: 99%